Scattergories Game on Junior High School Students’ Vocabulary Mastery in Language Learning - Anggraini, Dwi Liza; Salmiah, Maryati (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This article aims to determine the effect of using Scattergories Game on students' vocabulary mastery. The method used is a pre-experimental design with a quantitative approach. The population that was the research subject was 8th grade students at one of the MTs in Sampali. Consisting of 30 students in it. The researcher gave a pre-test - treatment – post-test to all samples to collect the required data. After that, the data was processed using the T-test in SPSS. The result showed that there is a significant influence between variable X on variable Y and decision making because sig .000 <0.05 and the average score on the post test (25.36) was higher than pre-test (13.63). From the results of data processing carried out by researchers, it can be concluded that the Scattergories game has an effect on students' vocabulary mastery Keywords: Effect, Scattergories Game, Vocabulary Mastery